Entre príncipes de la libertad y vecinos leales: la revuelta de los Contreras y la defensa de Panamá en 1550 - Jorge Díaz Ceballos (Nuevo mundo - Mundos Nuevos, 2018)
This work analyses the attack of the Contreras brothers to Panama City in April 1550 and the organization of the defense of the city by its inhabitants. A new interpretation of the creation of a collective memory that reinforced the corporate identity will be created through the testimonies of the protagonists, both attackers and defenders. The accounts of the individuals that participated in the action offer a counterpoint to the official narratives according to which this episode has been interpreted. The analysis of the facts and the political language implied, this article deals with the heuristic possibilities opened by political conflicts for the analysis of processes of definition of loyalty and obedience between the Crown and local communities of the Hispanic Monarchy.